Pre-extension demonstration of black pepper (Piper nigrum Linn.) technologies in selected districts of Ethiopia - Bekele, Teka Tefera; Getahun, Bethlehem; Toga, Thomas (International Journal of Agricultural Research, Innovation and Technology, 2025)
Black pepper (Piper nigrum Linn.), known as the "King of Spices," is a high-value crop with significant economic and medicinal importance. This study evaluates the pre-extension demonstration of black pepper technologies in selected districts of Southwest Ethiopia and Gambella Region, focusing on two improved varieties, Gacheb and Tato, under real-world farming conditions. The study involved 66 farmers across Yeki, Sheko, and Godere districts, aiming to enhance farmers' knowledge and skills in black pepper production, management, and post-harvest handling. Data were collected on agronomic performance, economic viability, and farmer perceptions. Results showed that both varieties adapted well to local conditions, with Gacheb exhibiting higher yield potential (2-3 kg/vine/year) compared to Tato (1.5-2.5 kg/vine/year). Economic analysis revealed a benefit-cost ratio of 4.71 for Gacheb and 4.29 for Tato, indicating profitability. Farmers expressed positive perceptions of black pepper's adaptability and financial benefits, ranking it second in priority after coffee. However, challenges such as pests, diseases, and inadequate knowledge in certain cultivation practices were identified. The study recommends capacity-building programs, development of resilient varieties, scaling-up demonstrations, and strengthening research-extension-farmer linkages to promote sustainable black pepper production. These efforts can enhance productivity, improve livelihoods, and support the wider adoption of black pepper technologies in Ethiopia. Int. J. Agril. Res. Innov. Tech. 15(1): 70-77, June 2025